Clot Formation Is Associated With Fibrinogen and Platelet Forces in a Cohort of Severely Injured Emergency Department Trauma Patients. (August 2015) - White, Nathan J.; Newton, Jason C.; Martin, Erika J.; Mohammed, Bassem M.; Contaifer, Daniel; Bostic, Jessica L.; Brophy, Gretchen M.; Spiess, Bruce D.; Pusateri, Anthony E.; Ward, Kevin R.; Brophy, Donald F.
Abstract : ABSTRACT: Introduction: Anticoagulation, fibrinogen consumption, fibrinolytic activation, and platelet dysfunction all interact to produce different clot formation responses after trauma. However, the relative contributions of these coagulation components to overall clot formation remain poorly defined. We examined for sources of heterogeneity in clot formation responses after trauma.Methods: Blood was sampled in the emergency department from patients meeting trauma team activation criteria at an urban trauma center. Plasma prothrombin time of 18 s or longer was used to define traumatic coagulopathy. Mean kaolin-activated thrombelastography (TEG) parameters were calculated and tested for heterogeneity using analysis of means. Discriminant analysis and forward stepwise variable selection with linear regression were used to determine if prothrombin time, fibrinogen, platelet contractile force (PCF), and D-dimer concentration, representing key mechanistic components of coagulopathy, each contribute to heterogeneous TEG responses after trauma.Results: Of 95 subjects, 16% met criteria for coagulopathy. Coagulopathic subjects were more severely injured with greater shock and received more blood products in the first 8 h compared with noncoagulopathic subjects. Mean (SD) TEG maximal amplitude (MA) was significantly decreased in the coagulopathic group (57.5 [SD, 4.7] mm vs. 62.7 [SD, 4.7], t test P < 0.001). The MA also exceeded the ANOM predicted upper decision limit for the noncoagulopathic group and the lower decision limit for the coagulopathic group at α = 0.05, suggesting significant heterogeneity from the overall cohort mean. Fibrinogen and PCF best discriminated TEG MA using discriminant analysis. Fibrinogen, PCF, and D-dimer were primary covariates for TEG MA using regression analysis.Conclusions: Heterogeneity in TEG-based clot formation in emergency department trauma patients was linked to changes in MA. Individual parameters representing fibrin polymerization, PCFs, and fibrinolysis were primarily associated with TEG MA after trauma and should be the focus of early hemostatic therapies.